Sustentabilidade e gestão da pesca artesanal na costa do Semiárido Potiguar (RN), Brasil - Maia, Ivanilson de Souza (2014)
T he socio - economy of the coastal municipalities of Rio Grande do Norte semiarid coast was analyzed th r ou g h by the actors, ant hropogenic implications, fishing environment and composition of its fish fauna, as well as the trend of product ion landed by the artisanal fleet with the aim of identifying the sustainability and management. In this study, were used participatory methodologies, monthly data of rainfall between September 2001 and December 2010; landings of the artisanal fleet during January 2001 to December 2010; and socioeconomic (IBGE, 2002/2010), (IDEMA, 2011/2012), (MPA, 2010; 2012), UNDP and MS (2013). Based on these data, we performed analysis of variance were performed using the method of Analytic Hierarchy Process (HAP) and s tatistical models of multiple regression and time series. It was identified that the occupation of the coastal and marine zone through salt industry, tourism, shrimp farming, oil and gas and wind energy reconfigured the environment and attracted new actors . Rainfall influenced the catches, of which 35% occur in the rainy season, 40% in the dry season and 25% independent. Production increased 55%, in the period analyzed , being landed in 31 ports spread over 11 municipalities, cap tured in environments mangrov e/ estuarine (23%), coastal (46%) and oceanic (31%). Despite market up 41 species, were commercialized in the region production concentrated in eight, mainly landed in Macau and Caiçara North, by vessels of small and medium - sized (motorized and sailboats) . Highlights included three species ( Hirundichthys affins , Coryphaena hippurus and Opisthonema oglinum ), which together accounted for 63.3% of the whole volume. It was found that the motorized vessels tripled in number while sailboats reduced by half. Landin gs by different types of vessels tend to increase over time, while the small sailboats vessels, decrease. The introduction of more new motorized vessels and sailboats also tend to increase production. The study concluded that GDP and HDI of coastal countie s increased however inequality persisted. The potential of artisanal fishing is in the stage “ unfavorable ” of development and the trend in fish production is to grow over time and with the entry of more vessels. However, it is urgent that the state actions to promote and enhance planning to restore fish stocks in a sustainable and profitable fisheries standards. Therefore, it is recommend the strategic use of natural resources in a sustainable development perspective.